2009
DOI: 10.1002/ajh.21547
|View full text |Cite
|
Sign up to set email alerts
|

Management of hematological malignancies during pregnancy

Abstract: The management of hematological malignancies during pregnancy is a challenging endeavor, which not only requires technical skills and knowledge by the clinicians but also requires sound clinical judgment and compassion, keeping in mind the patient and family preferences and, ultimately, the wellbeing of the neonate. The incidence of hematological malignancies during pregnancy is rare, ranging from 1 in 1,000 to 1 in 10,000 deliveries, impeding the design and execution of large prospective studies. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 160 publications
(227 reference statements)
1
56
0
8
Order By: Relevance
“…It can be extremely difficult during early stages to differentiate pregnancy-related physiologic changes from the subtle, early signs of an evolving acute malignancy, and this mimicry may delay a cancer diagnosis. 1,[8][9][10][11][12][13] Interestingly, a recent systematic review of nonHodgkin lymphoma (NHL) in pregnancy observed that aggressive forms of NHL exhibit unique clinical and biological features during pregnancy, including frequent involvement of the reproductive organs (breast, ovary, uterus, and placenta).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be extremely difficult during early stages to differentiate pregnancy-related physiologic changes from the subtle, early signs of an evolving acute malignancy, and this mimicry may delay a cancer diagnosis. 1,[8][9][10][11][12][13] Interestingly, a recent systematic review of nonHodgkin lymphoma (NHL) in pregnancy observed that aggressive forms of NHL exhibit unique clinical and biological features during pregnancy, including frequent involvement of the reproductive organs (breast, ovary, uterus, and placenta).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise extreme caution; use where benefit to mother clearly outweighs risk to fetus. Vincristine 1,11,16,45 No congenital anomalies or neurotoxicity documented.…”
Section: 28mentioning
confidence: 99%
See 3 more Smart Citations